A construção do atendimento em um núcleo de medidas socioeducativas em meio aberto - Munhoz, Sara Regina (Universidade Federal de São Carlos, 2013)
This research aims to discuss the data from my ethnography of an assistance nucleus (MSE / MA) to adolescents who practices infractions in the East Zone of São Paulo. The ethnography was conducted with a team of professionals that assists these boys, and emphasizes the perceptions that these professionals have of the construction of assistance, and the relationships they establish with the boys, with the judiciary and other government agencies. I describe the ways the team handles, on the one hand, with the rigidity of established goals by judges and described in the legislation and, on the other hand, with requirement also legal that assistances are individualized. To deal with these two logics, and present to the judges the knowledge that can only be built from the nucleus, technicians use the writing and interpretation of documents as their main weapons. It is a routine exercise of building arguments that justify the paths taken in each assistance. I also describe the frequent moments that the technicians can not extend their perceptions to the judiciary, causing divergent views on the progress of cases. I argument, therefore, that the relationship between the team and the judges is always based on the uncertainty and the definition of assistance needs to be negotiated in each case. This uncertainty manifests itself by the coexistence, in the nucleus, of different knowledge and different forms of governance of the boys.
Keywords: Antropologia social; Medidas socioeducativas; Atendimento; Delinquência juvenil; CIENCIAS HUMANAS::ANTROPOLOGIA